2020
DOI: 10.1002/jia2.25514
|View full text |Cite
|
Sign up to set email alerts
|

An implementation study of oral and blood‐based HIV self‐testing and linkage to care among men in rural and peri‐urban KwaZulu‐Natal, South Africa

Abstract: IntroductionIn South Africa, HIV‐infected men are less likely than women to test and know their status (the first UNAIDS “90‐90‐90” target), and men have worse outcomes across the HIV care cascade. HIV self‐testing (HIVST) may address this testing disparity but questions remain over the most effective distribution strategy and linkage following a positive test result. We implemented a men‐focused HIVST distribution programme to evaluate components contributing to participation and retention.MethodsWe conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
3
36
1
Order By: Relevance
“…Studies have shown promising practices among the different approaches targeting men/male for improved HIV testing, prevention, treatment, care and support services. [43][44][45][46][47][48][49][50][51][52][53] Health facility-level factors We found significant variation in outcomes attributable to differences at the health facility level. The variations across facilities remained statistically significant, even after controlling for individual-level and facility-level factors (Models 2 and 3).…”
Section: Individual-level Factorsmentioning
confidence: 78%
“…Studies have shown promising practices among the different approaches targeting men/male for improved HIV testing, prevention, treatment, care and support services. [43][44][45][46][47][48][49][50][51][52][53] Health facility-level factors We found significant variation in outcomes attributable to differences at the health facility level. The variations across facilities remained statistically significant, even after controlling for individual-level and facility-level factors (Models 2 and 3).…”
Section: Individual-level Factorsmentioning
confidence: 78%
“…In the study area, more than 20% of the residents migrate at least once in a given year, putting them at a higher risk of HIV acquisition and lack of access to HIV testing, prevention, or treatment services [45]. Other innovative approaches have been shown effective to increase the uptake of HCT such as provision of HIV self‐testing kits during delivery of home‐based HIV testing services [46], at the community [47], or through female partners attending antenatal care clinics [19] as well as finding men and offering tests at convenient locations (e.g. workplace) or via mobile testing [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Linkage to HIV care remains a critical challenge across HIVST studies [ 49 , 50 ]. In a recent implementation study of oral and blood-based HIV self-testing and linkage to care among men in rural and peri-urban KwaZulu-Natal, South Africa, Shapiro, van Heerden, Krows, et al [ 49 ] found 32% of HIV-positive men did not link to HIV care after 2 months of their initial HIVST positive result citing lack of time to go to clinic, having to be at work during the hours that the clinic is open, and being concerned about long wait times at the HIV clinic. These findings suggest a need for interventions that can reach men at their work place, or those that can reduce the need to go to the HIV clinic for HIV care.…”
Section: Discussionmentioning
confidence: 99%